2023
DOI: 10.3390/met13061051
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of the Transversal Rupture Strength (TRS) and Hardness of WC-Co Specimens Made via Additive Manufacturing and Sinter-HIP

Abstract: This study is focused on the mechanical properties of WC-Co composites obtained via Selective Laser Sintering (SLS) using PA12 as a binder. The as-printed samples were thermally debonded and sintered, first in a vacuum, and then sinter-HIP (Hot Isostatic Pressure) at 1400 °C, using 50 bar Ar, which has led to relative densities up to 66%. Optical metallographic images show a microstructure consisting of WC, with an average grain size in the range of 1.4–2.0 µm, with isolated large grains, in a well-distributed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…It was found that the relationship between the hardness of WC-Co and the average distance between the grains of cemented carbide is feasible, which is related to its microstructure [10]. Among the ultra-fine cemented carbide grades, where the WC grain size is <0.5 µm, the parts exhibit high hardness, which can prevent deep penetration of abrasives and thus have high wear resistance [11].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the relationship between the hardness of WC-Co and the average distance between the grains of cemented carbide is feasible, which is related to its microstructure [10]. Among the ultra-fine cemented carbide grades, where the WC grain size is <0.5 µm, the parts exhibit high hardness, which can prevent deep penetration of abrasives and thus have high wear resistance [11].…”
Section: Introductionmentioning
confidence: 99%
“…The second group includes multiple-step processes, in which forming and densification are performed at separate stages with different equipment. Namely, the most relevant are as follows: fused deposition modelling (FDM) [12,13], selective laser sintering (SLS) [14], in which the fusion occurs only in the polymer shells of the powders, and binder jetting additive manufacturing (BJAM) [15][16][17][18]. Multi-step processes combine the forming of a green-body with a subsequent thermal treatment (debinding-sintering) as in traditional powder metallurgy.…”
Section: Introductionmentioning
confidence: 99%